2006
DOI: 10.1016/j.febslet.2005.12.089
|View full text |Cite
|
Sign up to set email alerts
|

High expression of N‐acetylglucosaminyltransferase V in favorable neuroblastomas: Involvement of its effect on apoptosis

Abstract: Neuroblastoma (NBL), derived from the sympathetic precursor cells, is one of the most common pediatric solid tumors. The expression of N-acetylglucosaminyltransferase V and IX (GnT-V and GnT-IX) mRNA in 126 primary NBLs were quantitatively analyzed and higher expression levels of GnT-V were found to be associated with favorable stages (1, 2 and 4s). Conversely, the downregulation of GnT-V expression by small interfering RNA resulted in a decrease in the susceptibility to cell apoptosis induced by retinoic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 24 publications
(42 reference statements)
2
29
0
Order By: Relevance
“…In the current study, we found that MGAT5 was expressed in the Numerous studies have been confirmed a upregulation of MAGT5 in human tumors, such as breast cancer [20], colon carcinoma [22] and that upregulation of MGAT5 suggests favorable prognosis for bladder carcinoma [32], non-small cell lung cancer [33] and neuroblastoma [34]. primary trophoblast cells, is that it both reflects the complicated relationship between different types of cells and maintains the integrity of the tissue structure [36].…”
Section: Discussionsupporting
confidence: 54%
“…In the current study, we found that MGAT5 was expressed in the Numerous studies have been confirmed a upregulation of MAGT5 in human tumors, such as breast cancer [20], colon carcinoma [22] and that upregulation of MGAT5 suggests favorable prognosis for bladder carcinoma [32], non-small cell lung cancer [33] and neuroblastoma [34]. primary trophoblast cells, is that it both reflects the complicated relationship between different types of cells and maintains the integrity of the tissue structure [36].…”
Section: Discussionsupporting
confidence: 54%
“…Previous reports on the relationship between GnT-V expression and the prognosis in various cancers were controversial (8,11,12,17,18), but our data strongly suggested that it depends on the histological type, as well as the original organ of the cancer. In mucinous ovarian tumors, GnT-V was increased in cancer cells compared to benign and atypical borderline tumor cells.…”
Section: Discussionmentioning
confidence: 66%
“…Upregulated GnT-V activity has been reported in human colon cancer, hepatocarcinoma and breast cancer tissues (6)(7)(8)34). However, increased GnT-V activity has been found to be associated with favorable stages as well as favorable prognosis in non-small cell lung cancers, bladder carcinomas and neuroblastoma (9)(10)(11). In the present study, we investigated the role of GnT-V in gastric cancer during the process of metastasis and invasion.…”
Section: Expression Of Invasion-related Factors In the Bgc823/gnt-v Cmentioning
confidence: 99%
“…In the case of colon cancer and hepatocarcinoma, for instance, high GnT-V expression is associated with a poor prognosis (6)(7)(8). In contrast, low GnT-V levels are linked to a poor prognosis in lung, bladder carcinoma and neuroblastoma patients (9)(10)(11). The role of GnT-V in gastric cancer and its invasive behavior has scarcely been studied.…”
Section: Introductionmentioning
confidence: 99%